Peterson's graduate and professional : (Thomson Peterson's, 2006)
This comprehensive first book of a six-volume set includes institutional profiles indicating the degrees offered, enrollment figures, admission and degree requirements, tuition, financial aid, housing, faculty, research projects and facilities, and contacts at more than 2,000 institutions. Features and benefits include: * Informative data profiles for more than 2,000 institutions with facts and figures on accreditation, faculty, students, degree requirements, application deadlines, expenses, financial support and application contacts. * More than 250 two-page In-Depth Descriptions written by the institution give complete details on graduate study. * Advice on the admissions process, financial support, and accreditation and accrediting agencies. * Appendixes list institutional changes since the last edition and abbreviations used in the guide.